2006
DOI: 10.1016/j.ijms.2005.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of doubly-protonated peptide ion populations labeled by H/D exchange with CD3OD

Abstract: Doubly-protonated bradykinin (RPPGFSPFR) and an angiotensin III analogue (RVYIFPF) were subjected to hydrogen/deuterium (H/D) exchange with CD 3 OD in a Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer. A bimodal distribution of deuterium incorporation was present for bradykinin after H/D exchange for 90 s at a CD 3 OD pressure of 4 × 10 −7 Torr, indicating the existence of at least two distinct populations. Bradykinin ion populations corresponding to 0-2 and 5-11 deuteriums (i.e., D 0 , D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Because differences in gas-phase structure will allow for different extents and relative rates of HDX, [14] m/z values consisting of multiple isomeric ion structures can be identified by the presence of multiple HDX populations for a given product ion m/z. The use of HDX to separate isomers has been previously demonstrated by other researchers, including Marshall and coworkers [15] for a series of bradykinins, Herrmann et al [16] for bradykinin and angiotensin analogues in combination with SORI, Lifshitz and coworkers [17] for isomers of serine octamers, and very recently by Polfer and coworkers for fragments of poly-glycine peptides [18] as well by Somogyi and Paizs to reveal b 2 ion structures [19]. For additional confirmation of the presence of different structures, IRMPD can be used to fragment ions that have been separated by differences in HDX rates.…”
mentioning
confidence: 83%
“…Because differences in gas-phase structure will allow for different extents and relative rates of HDX, [14] m/z values consisting of multiple isomeric ion structures can be identified by the presence of multiple HDX populations for a given product ion m/z. The use of HDX to separate isomers has been previously demonstrated by other researchers, including Marshall and coworkers [15] for a series of bradykinins, Herrmann et al [16] for bradykinin and angiotensin analogues in combination with SORI, Lifshitz and coworkers [17] for isomers of serine octamers, and very recently by Polfer and coworkers for fragments of poly-glycine peptides [18] as well by Somogyi and Paizs to reveal b 2 ion structures [19]. For additional confirmation of the presence of different structures, IRMPD can be used to fragment ions that have been separated by differences in HDX rates.…”
mentioning
confidence: 83%
“…Working solutions (1.1765 ϫ 10 Ϫ5 M) were obtained by dilution in water. The injection solutions were prepared by adding the appropriate amount of MeOH to obtain a MeOH/H 2 O ratio of 15/85 (vol/ vol) and an oligonucleotide concentration of 1.0000 ϫ 10 Ϫ5 M. For the injection solutions of the RNA hexanucleotide, NH 4 Ac was added to reduce sodium adducts. The NH 4 Ac concentration was equal to 50 mM.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The rate of gasphase H/D exchange has been shown to be a function of the reagent used for exchange (nature and concentration), the charge state of the biomolecule, the gasphase basicity/acidity of exchangeable sites, and the internal structure of the biomolecular ions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Probing the number of exchanged hydrogens and the H/D exchange kinetics makes it possible to distinguish ion populations and to elucidate their structural and thermochemical features.…”
mentioning
confidence: 99%
“…In earlier studies, Wysocki and Somogyi had shown that HDX of b ions often displays bimodal distributions, which can be rationalized by the presence of two different chemical structures [27,28]. Recent HDX studies by Solouki and coworkers also show similar trends [29].…”
mentioning
confidence: 94%